Repeated core temperature elevation induces conduit artery adaptation in humans - Carter, H.; Spence, Angela; Atkinson, C.; Pugh, C.; Naylor, L.; Green, D. (Springer-Verlag, 2014)
Purpose: Shear stress is a known stimulus to vascular adaptation in humans. However, it is not known whether thermoregulatory reflex increases in blood flow and shear can induce conduit artery adaptation. Methods: Ten healthy young volunteers therefore underwent 8 weeks of 3 × weekly bouts of 30 min lower limb heating (40 C) during which the upper body was not directly heated. Throughout each leg heating session, a pneumatic cuff was placed on one forearm and inflated to unilaterally restrict reflex-mediated blood flow responses. Results: Each bout of leg heating significantly increased brachial artery shear rate in the uncuffed arm (96 ± 97 vs 401 ± 96 l/s, P < 0.01), whereas no change was apparent in the cuffed arm (83 ± 69 vs 131 ± 76 l/s, P = 0.67). Repeated episodic exposure to leg heating enhanced brachial artery endothelial function (measured by flow-mediated dilation) in the uncuffed arm from week 0 (5.2 ± 1.9 %) to week 4 (7.7 ± 2.6 %, P < 0.05), before returning to baseline levels by week 8. No adaptation was evident in the cuffed arm. Conclusions: We conclude that repeated increases in core temperature, induced via lower limb heating, resulted in upper limb conduit artery vascular adaptation which was dependent upon increases in shear stress. To our knowledge this is the first study to establish a beneficial systemic impact of thermoregulatory reflexes on conduit artery function in humans.